Synthesis of Chitosan Derivative Compounds Through Chloroacetic Acid and Heparin Grafting and Their Application as Membrane Materials with Polyvinyl Alcohol (PVA) - Shihandhanu Primadian Taqwa; Muhammad Cholid Djunaidi; Retno Ariadi Lusiana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
A chitosan membrane modified with chloroacetic acid with heparin (hep) and polyvinyl alcohol (PVA) has been successfully prepared. Chitosan was modified with chloroacetic acid through a nucleophilic substitution reaction to form N-carboxyl methyl chitosan (N-CMC) and then combined with PVA. N-CMC/PVA grafting with heparin was conducted using the immersion method and produced N-CMC/PVA.g.Hep membrane. This study aims to obtain a membrane with the best chemical and physical characteristics and the highest creatinine transport. Membrane characterization includes water absorption test, tensile strength, thickness, biodegradation, resistance to pH, and transport of creatinine and vitamin B12. Chemical characterization of active groups and morphology using FTIR and SEM. The characterization results show that the reaction of grafting chitosan using chloroacetic acid produces N-carboxymethyl chitosan (N-CMC). The N-CMC/PVA membrane has a creatinine transport capacity of 19.61%. The N–CMC/PVA.g.Hep membrane has a creatinine transport capacity of 24.81%. Supporting PVA improves the hydrophilicity and mechanical strength of the membrane.